NO removal efficiency of high-yield carbon nitride irradiated under various light sources. (January 2018) - Lu, Zhenzhen; Liu, Dong; Yang, Zhiyuan; Zhou, Jianting
Abstract: Graphitic carbon nitride (g-C3 N4 ) is a well-known photocatalyst. In this work, the NO removal efficiency of g-C3 N4 irradiated under various light sources is explored. For achieving high productivity and activity photocatalyst, the pyrolysis temperature is adjusted from 450 °C to 600 °C. All prepared g-C3 N4 are put into a transparent reaction box one by one to remove the NO with the initial concentration of 1000 ppb level in air flow under real indoor illumination of three light resources: metal halide lamp, LED lamp and high pressure sodium lamp. According to the photocatalytic reaction results, the NO removal ratio of g-C3 N4 synthesized under 500 °C can reach to 29.26% under the irradiation of metal halide lamp, overwhelming that of g-C3 N4 irradiated under other light sources. Several characterization methods were adopt to analyze the photocatalytic reaction mechanism and the micro structures of g-C3 N4 prepared from melamine. Because of the conduction band potential difference between g-C3 N4 and melem, heterojunction of melem and g-C3 N4 can form the convention-type charge transfer, which greatly reduce the combination ratio of photogenerated electrons and holes, thus enhance the photocatalytic activity of g-C3 N4 under the irradiation of metal halide lamp indicating why the g-C3 N4 synthesized under 500 °C possesses the best NO removal efficiency among these samples. In addition, compared with other lamps, metal halide lamp is proved to be the most suitable light resource to motivate g-C3 N4 because of its relatively concentrated light intensity. The present work provide us new perspectives for selecting suitable light resources and proper synthesis conditions for the generation of g-C3 N4 to achieve better air purification performance in tunnels and indoors.